Perceived roles of information communication technologies (ICTs) for agricultural production among smallholder farmers in Oyo State - Ologundudu, O.M.; Eniola, P.O. (ADAN JOURNAL OF AGRICULTURE, 2024)
The use of ICT for agricultural information dissemination in the agrarian communities can help enhance agricultural production. This study examined the usage and effect of information and communication technology for agricultural production among smallholder farmers in Oyo State. Objectives of the study included to ascertain the types of ICTs used for agricultural production, assess respondents’ knowledge on use of ICT for agricultural production and to examine the effect(s) of ICT on agricultural production among smallholder farmers in the study area. Multi stage sampling technique was used to select respondents from 5 rural LGAs of Oyo State to give 120 smallholder farmers. Interview schedule was used to elicit information from the respondents. Descriptive and inferential statistics such as Chi-Square and Pearson Product Moment Correlation were adopted to analyze data. Findings revealed that the mean age of respondents was 36.41±10.88 years and most cultivated crops in the study area were leafy vegetables (21.3%), cassava (18.8%) and maize (15.0%). Animals reared included poultry birds (28.8%), rabbit (5.0%), goat (2.5%) and cattle (2.5%). Mean years of farming experience was 10.1±5.95 years with average monthly income of N31,232.5±N16,074.53. ICT tools utilized for agricultural information included mobile phones ( ̅=1.91), radio ( ̅=1.89) and television ( ̅=1.38). Respondents’ knowledge on use of ICT for agricultural information was high (62.5%). Constraints encountered on use of ICT included inadequate infrastructural facilities ( ̅=1.51), insufficient income ( ̅=1.08) and poor electricity ( ̅=1.03). Effects of ICT on agricultural production included increased awareness on market ( ̅=1.90), personal skill development ( ̅=1.90) and increased knowledge on production ( ̅=1.90). Significant relationship exists between respondents’ education (χ2=11.139), knowledge (r=0.407) and effect of ICT on agricultural production. It was recommended that older farmers should be encouraged to improve on their educational background through improved extension services and there should be access to better infrastructural and financial facilities.